Monometal and competitive sorption of heavy metals in mine soils: Influence of mine soil characteristics - Mouni, Lotfi (Université de Bouira, 2013)
The environmental and health effects of the contamination of soils by heavy metals depend on the ability of the soils to immobilize these contaminants. This study was conducted to assess the monometallic and competitive sorption of lead, copper, zinc and cadmium in surface samples of four soils from eastern Algeria. Sorption isotherms were characterized using Freundlich and Langmuir equations. Retention selectivity sequences indicate that, in most ofthe soils, Pb isthe preferred retained metal, followed by Cu. The last metals in these sequences are Cd and Zn. All soils showed greater sorption capacity. On the basis of distribution coefficient values for the metal concentration of 100 mg. l -1 (Kd100) for each soil and trace element, the two most common adsorption sequences found were Pb>>Cu>Cd>Zn and Pb>>Cu>Zn>Cd. Competition significantly reduced metal Kd, especially that of Cd
Keywords: Competitive adsorption; Soil; Heavy metals; Distribution coefficient